2017
DOI: 10.5194/amt-10-3821-2017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water adsorption and hygroscopicity of atmospherically relevant particles using a commercial vapor sorption analyzer

Abstract: Abstract. Water adsorption and hygroscopicity are among the most important physicochemical properties of aerosol particles, largely determining their impacts on atmospheric chemistry, radiative forcing, and climate. Measurements of water adsorption and hygroscopicity of nonspherical particles under subsaturated conditions are nontrivial because many widely used techniques require the assumption of particle sphericity. In this work we describe a method to directly quantify water adsorption and mass hygroscopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 56 publications
(66 reference statements)
4
60
1
Order By: Relevance
“…Such kinds of mineral dust particles coated with anthropogenic pollutants have been observed by a number of previous electro-microscopic-based studies. Previous studies (Reitz et al, 2011;Gu et al, 2017;Ma et al, 2013) also demonstrated the presence of cSO 4 on the surface of dust particles; nevertheless, we think the effect of cSO 4 on the decrease in δ Dp=5 value was negligible because the mass fraction of cSO 4 was tiny (< 0.02) and the CaSO 4 was hard to dissolve in limited amounts of aerosol liquid water content. Note that the chemical compounds (such as kaolinite, illite, humic matter, etc.)…”
Section: Impact Of Heterogeneous Reactions On δ Values Of Particlesmentioning
confidence: 59%
See 1 more Smart Citation
“…Such kinds of mineral dust particles coated with anthropogenic pollutants have been observed by a number of previous electro-microscopic-based studies. Previous studies (Reitz et al, 2011;Gu et al, 2017;Ma et al, 2013) also demonstrated the presence of cSO 4 on the surface of dust particles; nevertheless, we think the effect of cSO 4 on the decrease in δ Dp=5 value was negligible because the mass fraction of cSO 4 was tiny (< 0.02) and the CaSO 4 was hard to dissolve in limited amounts of aerosol liquid water content. Note that the chemical compounds (such as kaolinite, illite, humic matter, etc.)…”
Section: Impact Of Heterogeneous Reactions On δ Values Of Particlesmentioning
confidence: 59%
“…Such a characteristic is widely used to distinguish dust and spherical particles by both ground-based lidar observations (Asian Dust and Aerosol Lidar Observation Network, AD-Net; Shimizu et al, 2016) and satellite remote sensing (Cloud-Aerosol Lidar with Orthogonal Polarization, CALIOP; on board the CALIPSO satellite; Winker et al, 2009;Zhang et al, 2018) presuming that spherical particles and dust were externally mixed. On the basis of this technique, studies on spatially resolved distributions Uno et al, 2008), transport patterns ) of pollution and dust, and data processing algorithms (Nishizawa et al, 2007(Nishizawa et al, , 2011Winker et al, 2009) have been widely performed. For instance, Shimizu et al (2004) summarized the contributions of different aerosol types on the total backscattering coefficient at multiple sites in East Asia using three-channel Mie scatting lidar data.…”
Section: Introductionmentioning
confidence: 99%
“…Phys. Very recently, Tang and coworkers systematically evaluated the performance of a vapor sorption analyser to investigate hygroscopic properties of particles of atmospheric relevance (Gu et al, 2017b). The instrument, with its schematic diagram shown in Fig.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The vapor sorption analyzer was used to examine hygroscopicity of CaSO4•2H2O at 25 o C (Gu et al, 2017b), and the results are displayed in Fig. 5.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…5b, a relative mass change of < 0.025 % within 6 h could be accurately determined. This instrument was further employed to investigate hygroscopic properties of perchlorates (Gu et al, 2017a;Jia et al, 2018), Ca-and Mg-containing salts (Guo et al, 2019), and primary biological particles , which play significant roles in the environments of the Earth and Mars. To our knowledge, the VSA technique has not yet been used to explore hygroscopic properties of ambient aerosol particles.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%